High-voltage electrolyte of lithium ion battery with lithium-rich positive electrode and application of high-voltage electrolyte
Patent Information
- Application Number
- CN202411791690.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The oxidation and decomposition of lithium-rich cathode materials by commercial electrolytes at high voltages has intensified, resulting in interface damage and affecting the cycle stability and service life of lithium-ion batteries.
The synergistic additives containing fluorine-containing lithium salts and nitric acid groups are used to regulate the solvation structure of the electrolyte, and a stable, solid, thin and low-impedance CEI film is formed on the lithium-rich positive electrode to protect the positive electrode interface.
It significantly improves the high voltage compatibility of the electrolyte and the lithium-rich positive electrode, and improves the cycle stability and rate performance of lithium-ion batteries.
Smart Images

Figure CN119695272A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a high-voltage electrolyte for a lithium-rich positive electrode lithium-ion battery and applications thereof. Background Art
[0002] In recent years, the application of portable electronic products and electric vehicles has promoted the rapid development of lithium-ion batteries, but the ever-evolving application needs have put forward higher energy density requirements for lithium-ion batteries. Lithium-rich layered oxides (LLOs) cathode materials have the advantages of high energy density and low cost, and have broad application prospects. However, lithium-rich cathodes also have problems such as transition metal dissolution, irreversible release of lattice oxygen, and irreversible phase transformation of surface structure. The oxidative decomposition of commercial electrolytes under high voltage aggravates the structural damage on the surface of lithium-rich cathodes, affecting the cycle stability and service life of lithium-rich cathode lithium-ion batteries. Therefore, it is crucial to design and develop high-voltage electrolytes that match lithium-rich cathodes.
[0003] How to effectively protect the positive electrode interface, prevent the decomposition of solvent molecules from causing damage to the interface, achieve good compatibility between the electrolyte and the lithium-rich positive electrode, and improve the cycle stability and rate performance of lithium-rich positive electrode lithium-ion batteries is one of the technical problems that need to be urgently solved in this field.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode and its application to solve the above-mentioned technical problems.
[0006] The present invention is achieved in that:
[0007] In a first aspect, an embodiment of the present invention provides a high-voltage electrolyte for a lithium-rich positive electrode lithium-ion battery, which includes an organic solvent, a lithium salt, and a synergistic additive;
[0008] Based on the total mass of the high voltage electrolyte, the amount of the synergistic additive added is ≤5%;
[0009] The synergistic additive includes an additive A containing a fluorine-containing lithium salt and an additive B containing a nitric acid group in a mass ratio of (3.5-6): (2-3.5).
[0010] In a second aspect, an embodiment of the present invention provides a lithium-ion battery, which includes a positive electrode, a negative electrode and the aforementioned high-voltage electrolyte.
[0011] The present invention has the following beneficial effects:
[0012] The high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode provided by an embodiment of the present invention regulates the solvation structure of the high-voltage electrolyte by introducing synergistic additives, forms a stable, strong, thin, low-impedance CEI film on the lithium-rich positive electrode, protects the positive electrode interface, inhibits the decomposition of solvent molecules, improves the high-voltage compatibility of the electrolyte with the lithium-rich positive electrode, and improves the cycle stability and rate performance of the lithium-ion battery, which has important scientific research and practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0014] Figure 1 The high voltage electrolyte Li of Example 1 and Comparative Example 1 is 1.13 Mn 0.517 Ni 0.256 Co 0.097 O2|Li battery cycle performance diagram;
[0015] Figure 2 The high voltage electrolyte Li of Example 1 and Comparative Example 1 is 1.13 Mn 0.517 Ni 0.256 Co 0.097 O2|Li battery rate performance diagram;
[0016] Figure 3 The electrolyte Li of Comparative Example 1 1.13 Mn 0.517 Ni 0.256 Co 0.097 SEM image of the positive electrode of O2|Li battery after cycling;
[0017] Figure 4 The electrolyte Li of Example 1 1.13 Mn 0.517 Ni 0.256 Co 0.097 Scanning electron microscopy image of the positive electrode of O2|Li battery after cycling. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] The impact of lithium-ion battery electrolyte on battery performance mainly includes two aspects. One is the solvation structure of the electrolyte itself. When lithium ions migrate in the electrolyte, they cooperate with solvent molecules or anions to form a solvent sheath. Usually, free solvent molecules that do not participate in the coordination are mostly extremely unstable and easily oxidized and decomposed by superoxide on the positive electrode side, and damage the positive electrode surface. The second is the unstable interface film formed by the reaction between the electrolyte and the electrode. The strong coordination between the solvent molecules and the lithium ions allows them to follow the lithium ions into the layered structure of the positive electrode during the charge and discharge process, destroying the surface structure, and oxidizing and decomposing at the same time, forming an uneven organic CEI film with low ion conductivity, increasing the interface impedance, and hindering the transmission of lithium ions.
[0020] The present invention introduces synergistic additives to regulate the electrolyte solvation structure, and utilizes the preferential oxidation of the additives to form a strong, thin, low-impedance CEI film on the lithium-rich positive electrode to prevent cracks and surface decay, thereby improving the battery cycle performance and rate performance. The specific process is as follows:
[0021] In a first aspect, an embodiment of the present invention provides a high-voltage electrolyte for a lithium-rich positive electrode lithium-ion battery, which includes an organic solvent, a lithium salt, and a synergistic additive;
[0022] Based on the total mass of the high voltage electrolyte, the amount of the synergistic additive added is ≤5%;
[0023] The synergistic additive includes an additive A containing a fluorine-containing lithium salt and an additive B containing a nitric acid group in a mass ratio of (3.5-6): (2-3.5).
[0024] It should be noted that lithium salts play the role of providing conductive ions in lithium batteries, which is the core mechanism for lithium batteries to generate current; organic solvents play the role of dissolving lithium salts, allowing lithium salt electrolytes to form ions that can conduct electricity.
[0025] Adding additives to lithium salts has the following characteristics: (1) It can increase the ion transfer rate and efficiency, improve the electrochemical properties of electrode materials, and thus improve the battery's charge and discharge performance and cycle performance; (2) It can reduce the moisture and HF content in the electrolyte, thereby inhibiting the hydrolysis reaction of LiPF6 and improving the battery's safety and stability; (3) When the battery is fully charged or the voltage is higher than the operating voltage, the additives will be oxidized at the positive electrode and diffuse to the negative electrode to undergo a reduction reaction, thereby preventing overcharge and overdischarge and protecting the battery; (4) It can improve the interface stability between the electrolyte and the electrode, improving the battery's high and low temperature performance and its ability to prevent overcharge and overdischarge.
[0026] Due to the chemical instability of additives, they are prone to decomposition reactions at high temperatures or under specific conditions, producing side reactions or harmful substances; if the additive content is too high, it will cause battery damage or explosion, affect the conductivity of the electrolyte and the charge and discharge efficiency of the battery, reduce its service life, battery performance and safety, and cause waste of resources and increase investment costs; if the additive content is too low, the film is not formed completely, which may cause structural damage to the electrode material, thereby affecting the cycle performance of the battery, shortening its life and reducing its safety.
[0027] The organic solvent, lithium salt and necessary additives in the electrolyte are prepared in a certain proportion to optimize the performance and safety of the battery and ensure the efficient and stable operation of the lithium battery.
[0028] In an optional embodiment of the present invention, based on the total mass of the high-voltage electrolyte, the amount of the synergistic additive added is 0.3%-1%; the mass ratio of the fluorine-containing lithium salt additive A and the nitric acid group-containing additive (also referred to as the nitrogen-containing additive) B is (4.8-5.4): (2.8-3.2).
[0029] It should be noted that by adding synergistic additives to regulate the electrolyte solvation structure and utilizing the preferential oxidizing property of the additives, a strong, thin, low-impedance CEI film is formed on the lithium-rich positive electrode to prevent cracks and surface degradation, thereby effectively improving the battery's cycle performance and rate performance.
[0030] Among them, the addition amount of the synergistic additive is selected from any one of 0.3%, 0.4%, 0.5%, 0.8% and 1%, or other values within the range of 0.3%-1%; the mass ratio of the fluorine-containing lithium salt additive A and the nitric acid group-containing additive B is selected from any one of 4.8:2.8, 4.9:2.8, 5:3, 5.2:3.1, 5.4:3.2, or other values within the range of (4.8-5.4):(2.8-3.2).
[0031] In an optional embodiment of the present invention, the fluorine-containing lithium salt additive A is selected from at least one of lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF4), lithium bis(fluoromalonate)borate (LIFMDFB), lithium difluorophosphate (LiPO2F2) and lithium difluorobis(oxalato)phosphate (C4F2LiO8P); further at least one of LiPO2F2 and LiDFOB. The nitrate group-containing additive B is selected from at least one of potassium nitrate (KNO3), magnesium nitrate (Mg(NO3)2), lithium nitrate (LiNO3), sodium nitrate (NaNO3) and sodium nitrite (NaNO2).
[0032] In an optional embodiment of the present invention, the molar concentration of the lithium salt is 1 mol / L-4.2 mol / L; based on the total mass of the high-voltage electrolyte, the amount of organic solvent added is 0.57wt%-0.85wt%, and the amount of lithium salt added is 0.15wt%-0.43wt%.
[0033] It should be noted that the amount of organic solvent added can be selected from any one of 0.57wt%, 0.65wt% and 0.85wt%, or other values within the range of 0.57wt%-0.85wt%; the amount of lithium salt added can be selected from any one of 0.15wt%, 0.25wt%, 0.30wt%, 0.35wt% and 0.43wt%, or other values within the range of 0.15wt%-0.43wt%.
[0034] The molar concentration of the lithium salt is selected from any one of 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 4 mol / L and 4.2 mol / L, or other values within the range of 1 mol / L-4.2 mol / L according to actual needs.
[0035] In an optional embodiment of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (F2LiNO4S2), lithium bis(trifluoromethylsulfonyl)imide (C2F6LiNO4S2), lithium trifluoromethylsulfonate (CF3SO3Li), lithium perchlorate (LiClO4) and lithium hexafluoroarsenate (LiAsF6).
[0036] It should be noted that the choice of lithium salt has an important influence on the electrochemical window, cycle life, safety performance, etc. of the electrolyte.
[0037] In an optional embodiment of the present invention, the organic solvent is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate, ethyl methyl carbonate (EMC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate, vinylene carbonate, ethyl acetate, cyclopentane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0038] The choice of organic solvent has an important influence on the conductivity of the electrolyte, the cycle efficiency, reversible capacity and safety of the battery. The dielectric constant and viscosity of the organic solvent directly affect the conductivity and ion migration speed of the electrolyte. Solvents with high dielectric constants are conducive to the dissolution and dissociation of lithium salts, while solvents with low viscosity help to increase the migration rate of lithium ions.
[0039] Furthermore, the organic solvent is a composite reagent selected from any one of fluoroethylene carbonate / dimethyl carbonate (FEC / DMC), fluoroethylene carbonate / ethyl methyl carbonate (FEC / EMC) and ethylene carbonate / dimethyl carbonate (EC / DMC).
[0040] It should be noted that in the optional embodiments of the present invention, the composite organic solvent has better performance and advantages than a single organic solvent, mainly in the following aspects: (1) the composite organic solvent can ionize the lithium salt and exist in the form of an electrolyte, which can improve the conductivity of the battery, thereby improving the battery discharge efficiency and charging rate; (2) the composite organic solvent can control the voltage of the battery, thereby improving the stability and high temperature resistance of the battery; (3) the composite organic solvent can increase the capacity and life of the battery, and at the same time reduce the leakage and expansion of the battery.
[0041] In an optional embodiment of the present invention, the preparation method of the high voltage electrolyte comprises: at room temperature, in a glove box protected by an inert gas (O2<0.1ppm, H2O<0.1ppm), mixing an organic solvent, a lithium salt and a synergistic additive to react, and preparing a high voltage electrolyte after they are completely dissolved;
[0042] The reaction temperature is 35°C-45°C and the reaction time is 8h-20h.
[0043] Specifically, the preparation method of the high-voltage electrolyte is as follows: at room temperature, in an argon-protected glove box (O2<0.1ppm, H2O<0.1ppm), an organic solvent, a lithium salt and a synergistic additive are mixed and reacted at a temperature of 35°C-45°C for 8h-20h, and a clear and transparent solution is obtained after complete dissolution, that is, a high-voltage electrolyte is obtained;
[0044] It should be noted that the high voltage electrolyte is used to match the lithium-rich layered oxide positive electrode active material.
[0045] In a second aspect, an embodiment of the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode and the aforementioned high-voltage electrolyte.
[0046] In an optional embodiment of the present invention, the positive electrode active material of the lithium ion battery includes a lithium-rich layered oxide active positive electrode material or one of the lithium-rich layered oxide active positive electrode materials; for example, Li 1.13 Mn 0.517 Ni 0.256 Co 0.097 O2, etc.
[0047] The preparation of the positive electrode of the lithium-ion battery includes the following steps: grinding and mixing 80%-90% of the positive electrode active material and 5%-10% of the conductive agent acetylene black, adding 5%-10% of the polyvinylidene fluoride (PVDF) binder to mix, using 1-methyl-2-pyrrolidone (NMP) to adjust the viscosity, which is not included in the mass percentage composition of the positive electrode material; coating the positive electrode material on the surface of aluminum foil, and drying to obtain the positive electrode.
[0048] The negative electrode active material of the lithium-ion battery includes at least one of metallic lithium, metallic lithium alloy, natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon materials, silicon and silicides, among which metallic lithium and metallic lithium alloy are directly used as the corresponding negative electrode.
[0049] The preparation of the negative electrode of the lithium-ion battery includes the following steps: grinding and mixing 70%-80% of the negative electrode active material and 10%-15% of the conductive agent acetylene black, adding 10%-15% of the polyvinylidene fluoride (PVDF) binder to mix, using 1-methyl-2-pyrrolidone (NMP) to adjust the viscosity, which is not included in the mass percentage composition of the negative electrode material; coating on the surface of copper foil, and drying to obtain the negative electrode.
[0050] In an optional embodiment of the present invention, the lithium-ion battery is assembled using a standard button cell CR2032, with Li 1.13 Mn 0.517 Ni 0.256 Co 0.097 O2 is used as the positive electrode active material. The positive electrode active material, conductive agent acetylene black, and binder PVDF are mixed and ground in a ratio of 8:1:1 to make a positive electrode material, which is pressed onto the positive electrode current collector aluminum foil as the positive electrode. Lithium metal is used as the negative electrode. A glass fiber diaphragm and the selected electrolyte are used to complete the assembly in a high-purity argon (99.99%) glove box with a moisture content and an oxygen content of less than 0.1ppm. The assembled battery is sealed with a pressure of 50MP on a button battery sealer, and the next test is performed after standing for 12 hours. In other optional embodiments of the present invention, the ratio of the positive electrode active material, the negative electrode, and the positive electrode raw material can be reasonably adjusted according to actual conditions.
[0051] In an optional embodiment of the present invention, the assembled battery is subjected to a constant current charge and discharge test on a LAND battery tester, and the first cycle charge and discharge current density is 20 mA g -1 , cut-off voltage 2.0V-4.8V, cycle charge and discharge current density after the second cycle 200mA·g -1, cut-off voltage 2.0V-4 8V. The electrochemical window test is: assemble the prepared electrolyte into Li|SS (stainless steel) battery, and perform linear cyclic voltammetry test at high input force. The working electrode is a stainless steel sheet, and the counter electrode and auxiliary electrode are lithium metal. The voltage range is 2.0V-7.0V, and the scan rate is 1.0mV / s. The rate performance test is: the assembled battery is subjected to constant current charge and discharge test on the LAND battery tester, with a cut-off voltage of 2.0V-4.8V, at 0.1C, 0.3C, 0.5C, 1C, 2C, 3C and 0.1C (1C=200mA·g -1 ) times.
[0052] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0053] Example 1
[0054] This embodiment provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and a preparation method thereof comprises the following steps:
[0055] At room temperature, in an argon glove box, lithium salt LiPF6 was added to an organic solvent with a volume ratio of FEC:DMC of 1:9, and heated and stirred at 40°C for 8 hours. Subsequently, synergistic additives 0.5% LiPO2F2 and 0.3% LiNO3 were added, and heating and stirring were continued for 8 hours to obtain a clear and transparent liquid, which was allowed to stand for use as an electrolyte.
[0056] The concentration of the lithium salt is 4 mol / L. Based on the total mass of the high-voltage electrolyte, the amount of the lithium salt added is 0.35 wt%, and the amount of the organic solvent added is 0.65 wt%.
[0057] Example 2
[0058] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0059] Synergistic additives 0.5% LiPO2F2 and 0.3% NaNO3 were added.
[0060] Example 3
[0061] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0062] Synergistic additives 0.5% LiPO2F2 and 0.3% KNO3 were added.
[0063] Example 4
[0064] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0065] Synergistic additives 0.5% LiPO2F2 and 0.3% Mg(NO3)2 were added.
[0066] Example 5
[0067] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0068] Synergistic additives 0.5% LiDFOB and 0.3% LiNO3 were added.
[0069] Example 6
[0070] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0071] Synergistic additives 1% LiPO2F2 and 0.3% LiNO3 were added.
[0072] Example 7
[0073] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0074] The lithium salt concentration is 1 mol / L.
[0075] Example 8
[0076] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0077] The lithium salt concentration is 2 mol / L.
[0078] Example 9
[0079] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0080] Lithium salt LiPF6 was added into an organic solvent with a volume ratio of FEC:EMC of 1:9.
[0081] Example 10
[0082] This embodiment provides a high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, and the preparation method thereof differs from that of embodiment 1 in that:
[0083] Lithium salt LiPF6 was added into an organic solvent with a volume ratio of EC:DMC of 1:1, and the concentration of lithium salt was 1 mol / L.
[0084] Comparative Example 1
[0085] This comparative example provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and the preparation method thereof differs from that of Example 1 in that:
[0086] The mixture was heated and stirred at 40°C for 12 hours to obtain a clear and transparent liquid, which was allowed to stand and used as an electrolyte. No synergistic additives were added during this process.
[0087] Comparative Example 2
[0088] This comparative example provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and the preparation method thereof differs from that of Example 1 in that:
[0089] The lithium salt concentration is 2 mol / L. It is heated and stirred at 40°C for 12 hours to obtain a clear and transparent liquid, which is allowed to stand and used as an electrolyte. No synergistic additives are added in this process.
[0090] Comparative Example 3
[0091] This comparative example provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and the preparation method thereof differs from that of Example 1 in that:
[0092] The single additive added was 0.5% LiPO2F2.
[0093] Comparative Example 4
[0094] This comparative example provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and the preparation method thereof differs from that of Example 1 in that:
[0095] The single additive added was 0.3% LiNO3.
[0096] Comparative Example 5
[0097] This comparative example provides a high-voltage electrolyte for lithium-rich positive-electrode lithium-ion batteries, and the preparation method thereof differs from that of Example 1 in that:
[0098] Lithium salt LiPF6 was added to an organic solvent with a volume ratio of FEC:DMC of 3:7, and heated and stirred at 40°C for 12 hours to obtain a clear and transparent liquid, which was allowed to stand and used as an electrolyte. No synergistic additives were added in this process.
[0099] Experimental Example 1
[0100] In this experimental example, the electrolytes prepared in Example 1 and Comparative Example 1 were assembled into batteries, and the corresponding batteries were tested as follows:
[0101] The battery in this experiment is assembled using a standard button cell CR2032, with Li1.13 Mn 0.517 Ni 0.256 Co 0.097 O2 was used as the positive electrode active material. The positive electrode active material, conductive agent acetylene black, and binder PVDF were mixed and ground in a ratio of 8:1:1 to make the positive electrode material, which was pressed onto the positive electrode current collector aluminum foil as the positive electrode. Lithium metal was used as the negative electrode. Glass fiber diaphragm and the selected electrolyte were used to complete the assembly in a high-purity argon (99.99%) glove box with a moisture content and oxygen content of less than 0.1ppm. The assembled battery was sealed with a 50MP pressure on a button battery sealer and left to stand for 12 hours before the next test.
[0102] The assembled battery was subjected to constant current charge and discharge test on the LAND battery tester. The first cycle charge and discharge current density was 20 mA g -1 , cut-off voltage 2.0V-4.8V, cycle charge and discharge current density after the second cycle 200mA·g -1 , cut-off voltage 2.0V-4 8V. Among them, the model parameter of LAND battery tester is CT2001A.
[0103] The electrochemical window test is as follows: the prepared electrolyte is assembled into a Li|SS (stainless steel) battery, and a linear cyclic voltammetry test is performed at a high input voltage, with the working electrode being a stainless steel sheet, and the counter electrode and auxiliary electrode being lithium metal. The voltage range is 2.0V-7.0V, and the scan rate is 1.0mV / s.
[0104] The rate performance test is as follows: the assembled battery is subjected to constant current charge and discharge test on the LAND battery tester, with a cut-off voltage of 2.0V-4.8V, at 0.1C, 0.3C, 0.5C, 1C, 2C, 3C and 0.1C (1C = 200mA·g -1 ) times.
[0105] The first cycle discharge specific capacity and the capacity retention rate after 200 cycles are shown in Table 1; the high voltage electrolyte Li of Example 1 and Comparative Example 1 1.13 Mn 0.517 Ni 0.256 Co 0.097 O2|Li battery cycle performance Figure 1 , battery rate performance see Figure 2 .
[0106] Table 1 The first cycle discharge capacity and 200 cycle capacity retention rate data of the battery
[0107]
[0108]
[0109] Combined with the data in Table 1 Figure 1 and Figure 2 It can be seen that the cycle stability and rate performance of the lithium-rich cathode lithium-ion battery under the action of the synergistic additive in Example 1 are significantly improved, which is attributed to the synergistic effect of the nitrogen-containing additive and the fluorine-containing additive, which effectively constructs an excellent CEI film on the LLOs cathode. When the electrolyte contains a single additive, such as Comparative Examples 2 and 3, although the discharge specific capacity and cycle performance are improved compared with Comparative Example 1, they are still not as good as the electrolyte containing the synergistic additive (Examples 1-10), indicating that the CEI formed after the decomposition of the synergistic additive is more uniform and stable than that of the single additive, which inhibits the irreversible transformation of the surface structure of the LLOs cathode and improves the cycle stability of the battery.
[0110] Test Example 1
[0111] This test example is to test the electrolyte Li in Example 1 and Comparative Example 1. 1.13 Mn 0.517 Ni 0.256 Co 0.097 The positive electrode scanning electron microscope image of the O2|Li battery after cycling. The test instrument is a field emission scanning electron microscope, model SU8020. For specific results, see Figure 3 (Comparative Example 1) and Figure 4 (Example 1).
[0112] from Figure 3 and Figure 4 It can be seen that cracks exist on the surface of the positive electrode in Comparative Example 1, while there are no cracks on the surface in Example 1, indicating that the synergistic additive used in the present invention decomposes during the reaction to construct a stable and strong CEI film, protects the positive electrode structure from destruction, and inhibits the generation of intergranular cracks.
[0113] In summary, the high-voltage electrolyte for lithium-rich positive electrode lithium ion batteries containing synergistic additives provided in the embodiments of the present invention forms a stable, strong, low-impedance CEI film rich in LiF with high interfacial energy and Li3N with high ionic conductivity, thereby protecting the positive electrode interface; at the same time, the solvation structure of the electrolyte is regulated to prevent the destructive effect of solvent molecule decomposition on the interface, thereby achieving good compatibility between the electrolyte and the lithium-rich positive electrode, and significantly improving the cycle stability and rate performance of the lithium-rich positive electrode lithium ion battery.
[0114] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-voltage electrolyte for lithium-ion batteries with a lithium-rich positive electrode, characterized in that: The high voltage electrolyte includes an organic solvent, a lithium salt and a synergistic additive; Based on the total mass of the high voltage electrolyte, the amount of the synergistic additive added is ≤5%; The synergistic additive comprises an additive A containing a fluorine-containing lithium salt and an additive B containing a nitric acid group in a mass ratio of (3.5-6): (2-3.5).
2. The high voltage electrolyte according to claim 1, characterized in that: Based on the total mass of the high voltage electrolyte, the amount of the synergistic additive added is 0.3%-1%; The mass ratio of the additive A containing fluorine-based lithium salt to the additive B containing nitric acid groups is (4.8-5.4):(2.8-3.2).
3. The high voltage electrolyte according to claim 2, characterized in that: The fluorine-containing lithium salt additive A is selected from at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(fluoromalonate)borate, lithium difluorophosphate and lithium difluorobis(oxalate)phosphate; preferably at least one of lithium difluorophosphate and lithium difluorooxalatoborate; The additive B containing a nitric acid group is selected from at least one of potassium nitrate, magnesium nitrate, lithium nitrate, sodium nitrate and sodium nitrite.
4. The high voltage electrolyte according to claim 1, characterized in that: The molar concentration of the lithium salt is 1 mol / L-4.2 mol / L; Based on the total mass of the high-voltage electrolyte, the amount of the organic solvent added is 0.57wt%-0.85wt%, and the amount of the lithium salt added is 0.15wt%-0.43wt%.
5. The high voltage electrolyte according to claim 4, characterized in that: The organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate, vinylene carbonate, ethyl acetate, sulfolane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
6. The high voltage electrolyte according to claim 5, characterized in that: The organic solvent is a compound reagent, which is selected from any one of fluoroethylene carbonate / dimethyl carbonate, fluoroethylene carbonate / ethyl methyl carbonate and ethylene carbonate / dimethyl carbonate.
7. The high voltage electrolyte according to claim 4, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium perchlorate and lithium hexafluoroarsenate.
8. The high voltage electrolyte according to claim 1, characterized in that: The preparation method of the high voltage electrolyte comprises: At room temperature, in a glove box protected by inert gas, an organic solvent, a lithium salt and the synergistic additive are mixed and reacted to obtain the high-voltage electrolyte after they are completely dissolved; The reaction temperature is 35°C-45°C and the reaction time is 8h-20h.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and the high-voltage electrolyte according to any one of claims 1 to 8.
10. The lithium ion battery according to claim 9, characterized in that: The positive electrode active material of the lithium ion battery includes a lithium-rich layered oxide active positive electrode material or one of a lithium-rich layered oxide active positive electrode material; The negative electrode active material of the lithium ion battery includes at least one of metallic lithium, metallic lithium alloy, natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon material, silicon and silicide, wherein metallic lithium and metallic lithium alloy are directly used as the corresponding negative electrode.